Effects of Taraxacum officinale on Glioblastoma Cell Culture and Their Correlation with Hydroxycinnamic Acids Content - Ala Fulga; Ana Casian; Igor Casian; Svetlana Protopop; Valentin Gudumac; Olga Tagadiuc (Medical Sciences Forum, 2023)
Glioblastoma is an aggressive type of CNS tumor. The aim was to evaluate the antitumor activity of Taraxacum officinale (TO) extracts on U-138 MG glial cells and correlate it with the concentration of chicoric (ChA), chlorogenic (CGA), and caftaric (CA) acids (mg/mL) in the extract. TO dry leaves were extracted with DMSO (dimethyl sulfoxide) and ethanol of different concentrations. The concentration of acids was determined by liquid chromatograph (Agilent 1260 with DAD). The viability of U-138 MG cells was assessed by MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) test (% of viable cells). The activity of TO was compared with that of doxorubicin. The best antitumor activity was shown by TO extracts prepared with DMSO (110,000 µg/L—17.3 ± 8%, which contained ChA—8976 × 10−6 mg/mL, CGA—316.8 × 10−6 mg/mL, CA—1628 × 10−6 mg/mL), with 50% ethanol (150,000 µg/L—13.7 ± 3.2%, containing ChA—52,500 × 10−6 mg/mL, CGA—1746 × 10−6 mg/mL, CA—8460 × 10−6 mg/mL) and with 80% ethanol (40,000 µg/L—16.1 ± 9%, containing ChA—904 × 10−6 mg/mL, CGA—114.4 × 10−6 mg/mL, CA—70.4 × 10−6 mg/mL). TO extract activity was close to that of doxorubicin. In conclusion, the TO antitumor activity depends on the type of extractant and its concentration, as well as on the content of cinnamic acids.